Raza y nación en la poesía de Cristina Rodríguez Cabral - Jiménez, Luis A. (2006)
This study deals with the poetry of Afro-Uruguayan autor Cristina Rodríguez Cabral. It explores the concepts of race and nation within the complex mosaic of the historical and literary evolution of woman of African origin and her descendents in Uruguay.